PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK NUMBERED HEADS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 28 PADANG - Novita, Resi; K, Delsi.; Fitri, Dewi Yuliana (Pendidikan Matematika, 2013)
This research was conducted based on the fact that the studentsâ understanding on mathematics concept was still low and the students prefer to study in group, but the result is not appropriate with expectation. This research was aimed at revealing whether the use of cooperative learning Numbered Heads technique could improve the second year studentsâ understanding on mathematics concept better than that of conventional learning. Type of this research is experimental research which using Random subject as research design. The populations in this study were eighth grade students of SMP 28 Padang academic year 2013/2014. By using technique of Random sampling, the sample was selected the class VIII4 as experimental class and VIII6 as control class. This study used post-test as instrument to measure the studentsâ understanding mathematical concepts. The form of post-test is essay with a reliability r11 = 0,87 . The data analysis technique used t âtest by using MINITAB. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at the level of 95 % with Î± = 0.05 . Hypothesis test results obtained P - value equal to 0.015 means less than Î± = 0.05 , then the hypothesis in this study received so it can be concluded that the students understanding of mathematical concepts by using cooperative learning Numbered Heads technique is better than student understanding of mathematical concepts by conventional teaching class VIII SMP 28 Padang